PENETAPAN AGAMA DAN NASAB ANAK: Analisis Menurut Hukum Islam Pada Suami Isteri Dari Pernikahan Beda Agama - Farisi, Usman Al (Moderation | Journal of Islamic Studies Review, 2023)
Interfaith marriages often occur in society and this is a social fact that is sometimes difficult to resolve. This is a problem that never leads to an agreement on both sides, so that its presence always occupies two problems, namely there are opinions that allow and there are opinions that do not allow. Therefore, in response to this, Islamic Law as an applied law of the Religious Court, also does not escape discussing interfaith marriage in its articles and provides clear boundaries related to the marriage in the context of the benefit of Muslim life in Indonesia. Therefore, it can be concluded that children born to couples of different religions are considered valid as long as the interfaith marriage is legalized by a Judge's Decision and registered in the marriage registration office. Because a legitimate child according to the provisions of article 42 of the marriage law is a child born from a valid marriage based on article 2 paragraph (2). And Nasab the child does not have from civil law with his father, the child only has a civil relationship with the mother and his mother's family only.